Fostering Tolerance, Respect, and Diversity Values Through Civic Education in Indonesian Elementary Schools - Khosiah, Nur; Rahardjanto, Abdul Kadir; Sugiarti, Sugiarti (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to investigate how Civic Education (PKn) instills the values of diversity, tolerance, and mutual respect in elementary education. The research employed a qualitative case study design conducted at MI Miftahul Huda, Probolinggo. The data sources involved 30 fourth-grade students, 3 teachers, and 1 principal. Data collection techniques consisted of classroom observations, in-depth interviews, and document analysis, while data analysis followed an interactive model encompassing data reduction, data display, and conclusion drawing. The findings reveal that the internalization of diversity values is achieved through a holistic and integrative approach. This approach combines active learning methods (such as role-playing and group discussions), consistent daily practices in the school environment, and strong teacher role modeling. The study found significant positive impacts, including increased student engagement, the use of inclusive language, and behavioral shifts towards greater empathy and peer enforcement of respectful norms. In conclusion, this research highlights the strategic role of Civic Education in nurturing tolerant young citizens. It offers a practical framework for educators to strengthen character building in diverse educational contexts through collaborative school and community efforts, demonstrating that diversity education must move beyond theory to become a lived experience.